2015
DOI: 10.4014/jmb.1409.09035
|View full text |Cite
|
Sign up to set email alerts
|

A New-Generation Fluorescent-Based Metal Sensor – iLOV Protein

Abstract: The iLOV protein belongs to a family of blue-light photoreceptor proteins containing a lightoxygen- voltage sensing domain with a noncovalently bound flavin mononucleotide (FMN) as its chromophore. Owing to advantages such as its small size, oxygen-independent nature, and pH stability, iLOV is an ideal candidate over other reporter fluorescent proteins such as GFP and DsRed. Here, for the first time, we describe the feasibility of applying LOV domain-based fluorescent iLOV as a metal sensor by measuring the fl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
32
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 26 publications
(36 citation statements)
references
References 18 publications
4
32
0
Order By: Relevance
“…To determine if the Cu II ‐induced quenching was reversible, we added an equivalent amount of the metal chelator EDTA, and found that the fluorescence was restored to ≈85 % of the original fluorescence and was not further increased with additional chelator (Figure A, B). These results are similar to those previously observed for iLOV . Given that zinc and copper are two of the tightest‐binding biologically relevant metal ions, we also checked the reversibility of the modest Zn II ‐induced quenching.…”
Section: Resultssupporting
confidence: 87%
See 2 more Smart Citations
“…To determine if the Cu II ‐induced quenching was reversible, we added an equivalent amount of the metal chelator EDTA, and found that the fluorescence was restored to ≈85 % of the original fluorescence and was not further increased with additional chelator (Figure A, B). These results are similar to those previously observed for iLOV . Given that zinc and copper are two of the tightest‐binding biologically relevant metal ions, we also checked the reversibility of the modest Zn II ‐induced quenching.…”
Section: Resultssupporting
confidence: 87%
“…We set out to determine how the properties of CreiLOV are affected by the presence of biologically relevant metal ions. Previous work on iLOV demonstrated an inherent affinity for and quenching effects from the presence of Cu II , but CreiLOV has a higher quantum yield than iLOV and is more photostable . Furthermore, although the amino acids that interact with FMN are the same between the two proteins, the proposed metal‐binding amino acids of iLOV are two asparagine residues.…”
Section: Resultsmentioning
confidence: 98%
See 1 more Smart Citation
“…For instance, iLOV fluorescence is quenched in the presence of copper at physiological pH and is reversible in the presence of the metal ion chelator EDTA [35]. Two asparagine residues within the vicinity of the FMN fluorophore at positions 401 and 425 (based on the amino acid positions in Arabidopsis phototropin 2 from which iLOV was derived) are proposed to coordinate copper binding.…”
Section: Biosensor Applicationsmentioning
confidence: 99%
“…The site‐specific incorporation of tyrosine analogues not only yielded a pH sensor, but also system that selectively detects Mn(III) . Additionally, it was found that Cu(II) binds to iLOV with a K d of 4.7 µM and quenches its fluorescence selectively and reversibly . Unfortunately, neither of these sensors has been tested in live cell microscopy.…”
Section: Using Fluorogenic Proteins To Develop Biosensors To Detect Imentioning
confidence: 99%